2020
DOI: 10.1002/uog.21893
|View full text |Cite
|
Sign up to set email alerts
|

Maternal arterial stiffness in hypertensive pregnancies with and without small‐for‐gestational‐age neonate

Abstract: Objective Pregnancies complicated by pre‐eclampsia with a small‐for‐gestational‐age (SGA) neonate have poorer maternal hemodynamic function compared to those with hypertensive disorders of pregnancy (HDP) and an appropriately grown neonate. Arterial stiffness is a recognized prognostic marker of cardiovascular disease in the general population. The aim of this study was to compare maternal arterial stiffness between hypertensive pregnancies with, and those without, a SGA neonate and normotensive control pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A vicious cycle of enhanced placental OS can allow the release of leukocytes, neutrophils, and cytokines from the placenta, as well as further ROS into the maternal blood circulation, resulting in a massive systemic endothelial dysfunction. In cases where great endothelial damage is observed, arterial compliance is lower and vascular resistance is higher [36]. Furthermore, as widely demonstrated in the Framingham Heart Study [37], arterial stiffness acts as a predictor of cardiovascular disease, cognitive impairment, and dementia.…”
Section: Oxidative Stress In Preeclampsiamentioning
confidence: 88%
“…A vicious cycle of enhanced placental OS can allow the release of leukocytes, neutrophils, and cytokines from the placenta, as well as further ROS into the maternal blood circulation, resulting in a massive systemic endothelial dysfunction. In cases where great endothelial damage is observed, arterial compliance is lower and vascular resistance is higher [36]. Furthermore, as widely demonstrated in the Framingham Heart Study [37], arterial stiffness acts as a predictor of cardiovascular disease, cognitive impairment, and dementia.…”
Section: Oxidative Stress In Preeclampsiamentioning
confidence: 88%
“…Due to the COVID-19 pandemic, we will ask questions related to COVID-19 symptoms and capture information about COVID-19 vaccinations. For the mothers, we will conduct a basic cardiology assessment one year after the woman delivered using two devices, the arteriograph 20 to measure arterial stiffness and central pulse wave reflection, and the Ultrasonic Cardiac Output Monitor (USCOM) 21 to measure cardiac output and systemic vascular resistance. These data will be used to assess possible risk factors of cardiac disease.…”
Section: Non-clinical Datamentioning
confidence: 99%
“…The prevailing hypothesis is that the latter occurs secondary to maternal cardiovascular dysfunction in the face of increased pregnancy hemodynamic demands with advancing gestation [3][4][5][6][7][8][9][10] . Subsequent placental hypoperfusion leading to placental dysfunction may manifest as HDP or SGA birth [11][12][13] . Some researchers have suggested that cardiovascular profiling might facilitate the screening, diagnosis and management of placental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The prevailing hypothesis is that the latter occurs secondary to maternal cardiovascular dysfunction in the face of increased pregnancy hemodynamic demands with advancing gestation 3–10 . Subsequent placental hypoperfusion leading to placental dysfunction may manifest as HDP or SGA birth 11–13 .…”
Section: Introductionmentioning
confidence: 99%